2016
DOI: 10.1186/s12864-016-2885-x
|View full text |Cite
|
Sign up to set email alerts
|

Echinocandin B biosynthesis: a biosynthetic cluster from Aspergillus nidulans NRRL 8112 and reassembly of the subclusters Ecd and Hty from Aspergillus pachycristatus NRRL 11440 reveals a single coherent gene cluster

Abstract: BackgroundEchinocandins are nonribosomal lipopeptides produced by ascommycete fungi. Due to their strong inhibitory effect on fungal cell wall biosynthesis and lack of human toxicity, they have been developed to an important class of antifungal drugs. Since 2012, the biosynthetic gene clusters of most of the main echinocandin variants have been characterized. Especially the comparison of the clusters allows a deeper insight for the biosynthesis of these complex structures.ResultsIn the genome of the echinocand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 25 publications
1
20
0
Order By: Relevance
“…According to this study, the genes are arranged in two separate partial clusters (Ecd and Hty) located on different contigs of the assembly. However, we showed recently that Ecd and Hty can be aligned to a single cluster (Ecd/ Hty) and the disjunct genomic location of the cluster fragments was likely an artifact of genome misassembly in the absence of a reference genome [14]. It was also found that Ecd/Hty was virtually identical with a putative echinocandin B biosynthetic cluster AE deposited at the NCBI as a sequence of the producer strain Aspergillus delacroxii NRRL 3860 (formerly Emericella nidulans var.…”
Section: Introductionmentioning
confidence: 78%
See 3 more Smart Citations
“…According to this study, the genes are arranged in two separate partial clusters (Ecd and Hty) located on different contigs of the assembly. However, we showed recently that Ecd and Hty can be aligned to a single cluster (Ecd/ Hty) and the disjunct genomic location of the cluster fragments was likely an artifact of genome misassembly in the absence of a reference genome [14]. It was also found that Ecd/Hty was virtually identical with a putative echinocandin B biosynthetic cluster AE deposited at the NCBI as a sequence of the producer strain Aspergillus delacroxii NRRL 3860 (formerly Emericella nidulans var.…”
Section: Introductionmentioning
confidence: 78%
“…Table 5). Sequence analysis of PCR samples from the genomes of both strains, showed that the sequence of AE cluster is identical with that of A. pachycristatus, but not with A. delacroxii [14]. Moreover, a comparison of the calmodulin genes, a common taxonomic marker for fungi, suggested that strain NRRL 3860 belongs to the Aspergillus 40% feces, < 15% urine (< 1% unchanged) Tolerance Due to their specific mode of action, echinocandins are comparatively well tolerated.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The biosynthetic gene cluster of this strain has been identified and comprehensively characterized by the groups of Tang and Walsh (16,17). More recently, the sequence has been revised (21).…”
mentioning
confidence: 99%